WHEN LINES DON’T MEET: ANGLES AND TANGLES IN THE NON-FULFILLMENT OF THE TRIFOCAL FUNCTIONS OF TERTIARY FACULTY, NORTHWESTERN PHILIPPINES - Caiga, Nick (Journal of Education and Innovation, 2025)
This study focused on exploring the reasons why some faculty members face challenges in performing their three-fold functions of instruction, research, and extension services. The research aimed to determine the perspectives of the faculty members towards their three-fold functions, examined the factors affecting their performance in carrying out these functions, and the challenges they encountered. The study used phenomenological research design where 20 faculty members were interviewed. By delving into the perspectives and experiences of faculty members, the study seeks to understand their perceptions of their instructional, research, and extension roles. It also examined factors that influence their performance, such as institutional support, workload management, available resources, and opportunities for professional development. Additionally, the study identified and analyzed the challenges they face while fulfilling their functions. Findings showed that they exhibit a solid grasp of their responsibilities and find great fulfillment in teaching, research, and extension activities, however, they encounter several significant challenges such as limited involvement, heavy workloads, inadequate resources, and institutional obstacles that impede their effectiveness. Four themes emerge in the study namely: Faculty Perception and understanding, Affecting performance factors, Challenges encountered, and Enjoyment and fulfilment. The findings will provide valuable insights for developing targeted interventions and strategies to enhance faculty members’ performance and address the challenges they encounter. This research is aimed at supporting the faculty members of State Universities and Colleges in successfully fulfilling their three-fold functions.